(Invited) Skin-Mimic Hydrogel Materials with Water-Perspiration Control for Soft Robots Developed by 3D Printing. (8th September 2020) - Kanai, Shuma; Watanabe, Yosuke; Shiblee, MD Nahin Islam; Khosla, Ajit; Ogawa, Jun; Kawakami, Masaru; Furukawa, Hidemitsu
Abstract : Hydrogels are soft and wet materials with high biocompatibility, and are expected as a material for soft robots that have a touch similar to that of human skin. However, hydrogels have some technical drawbacks such as high-water evaporation rate, different touch and temperature from that of human skin. The purpose of this research is to reproduce a touch of hydrogels similar to the human skin. We designed a flow channel inside the hydrogel for supplying and circulating warm water to mitigate drying of the gel. With this mechanism mass loss due to drying was decreased by 43%. In addition, we found that coating hydrogels with solvent and polymer changes its surface friction coefficient.